PENGARUH REKONSTRUKSI PROFIL CAMSHAFT MESIN ASTRO 108 CC TERHADAP TORSI DAN DAYA - Nur Priyanto; Fadelan Fadelan; Yoyok Winardi (Universitas Muhammadiyah Ponorogo, 2021)
Nowadays motorcycle is the most used transportation in Indonesia and in overseas. Sometime the engine performance that is used by the rider is not maximal with the standard. Some sectors are re-modified to increase motorcycle’s engine performance. One o part that is modified is Camshaft to change the height of valve lift. The research purpose is to acknowledge the impact of the height of valve lift, power and torque. From the experiment of dynotest can be known that standard camshaft produces maximum power about 6,9 N.m at speed 4916 Rpm and the maximum torque is 7,76N.m at speed 7969 Rpm. The modified camshaft 1 produces power about 7,9 HP at speed 8481 Rpm and maximum torque is 7,28 N.m at speed 6844 Rpm. The modified Camshaft 2 produces power about 8,1 HP at speed 8538 Rpm and the maximum torque is about 7,29 N.m at speed 6973 Rpm. The power of modified camshaft 3 is about 8,4HP at speed 8872 rpm and the torque is about 7,23 N.m at 7085 rpm. The best power is on modified camshaft 3 with 8,4 HP and the best torque is in Standard Camshaft with 7,76 N.m.